Hubungan Peran Tenaga Kesehatan, Peran Orang Tua Dan Sikap Dengan Kejadian Anemia Pada Remaja Putri Di Sma Islam Terpadu Raflesia Kota Depok - Lala Monica; Sobar Darmaja; Nur Handayani (Politeknik Karya Husada, 2024)
Anemia has a negative impact on a teenager's health if it occurs continuously. Previous research shows that a female student who is anemic can experience decreased attention in class and also cognitive abilities, which has an impact on the length of the school graduation period. The purpose of this research is to determine the relationship between the role of health workers, the role of parents and attitudes with the incidence of anemia in young women at the Rafflesia Integrated Islamic High School, Depok City in 2023. The type of research used in this research is survey research with descriptive research and quantitative analysis with This research design uses a cross sectional design. The analysis test in this research uses Chi Square. The sampling technique uses Purposive Sampling technique. The sample obtained was 125 respondents. Based on the results of the Bivariate test, there is a significant relationship between the variables Role of Health Workers (p=0.000), Role of Parents (p=0.000), and Attitude (p=0.001). For Raflesia Integrated Islamic High School, Depok City, they can pay attention to their students and educate them more often about the importance of taking Fe tablets to avoid anemia.